Organizational and Strategy Impact Evaluation of CRM Implementation at Statistics Indonesia - Geri Yesa Ermawan; Achmad Nizar Hidayanto; Hari Prasetyo Tri Wicaksono (Green Publisher Indonesia, 2026)
The increasing adoption of digital systems in public sector organizations has positioned Customer Relationship Management (CRM) as a strategic instrument for improving service quality and organizational performance. This study aims to evaluate the organizational and strategic impacts of CRM implementation at Statistics Indonesia through the SILASTIK system. An applied research design with a case study approach was employed to examine CRM implementation within its institutional context. The evaluation was conducted using a multi-perspective performance evaluation framework focusing on organizational capital, human capital, customer retention, customer expansion, and customer perceived value. Data were collected through a structured questionnaire distributed to internal CRM users, open-ended survey responses, and a semi-structured interview with a key system stakeholder. Quantitative data were analyzed using descriptive analysis, while qualitative data were examined through thematic analysis and KPI categorization. The findings indicate that CRM implementation has contributed positively to organizational alignment, service coordination, and internal efficiency, particularly in terms of management commitment, knowledge sharing, and productivity. However, limitations were identified in behavior-oriented adoption, structured training mechanisms, system integration, and the systematic measurement of customer-oriented performance dimensions. Overall, the study demonstrates that CRM implementation at Statistics Indonesia has progressed beyond a technical system and now functions as an organizational enabler, although its strategic potential has not yet been fully realized. These findings provide empirical insights into CRM evaluation in public sector statistical institutions and offer a foundation for strengthening CRM governance and performance management.